PSYCHOLOGICAL IMPACT OF DYSMENORRHEA IN MEDICAL AND ALLIED HEALTH STUDENTS: EVIDENCE FROM NORTH INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Dysmenorrhea is a common gynecological condition associated with significant physical discomfort and psychological distress. Female healthcare students may be particularly vulnerable due to academic pressure and demanding schedules, yet its psychological impact is often overlooked. Aim and objectives: To assess the psychological impact of dysmenorrhea among female healthcare students. Method: A quantitative cross sectional study was conducted among 255 undergraduate medical and allied health students at a tertiary care university in North India using convenience sampling. Data were collected through an online questionnaire including sociodemographic details, DASS-21, MMDQ, and WaLIDD, and analyzed using descriptive and inferential statistics. Results: Dysmenorrhea prevalence was 88.6%, with 80% reporting adverse academic effects. Psychological distress was prevalent, with 54.5% depressive symptoms, 59.3% anxiety, and 38.4% stress. Menstrual distress was mild (48.6%), moderate (40.8%), and severe (15.7%). WaLIDD scores showed significant positive correlations with DASS-21 and MMDQ. Significant associations were observed with selected sociodemographic variables, while age, marital status, and caffeine intake were not associated. Conclusion: Dysmenorrhea represents a substantial psychological and academic burden among female healthcare students. Integrated menstrual and mental health interventions are essential to improve student well-being.